2022
DOI: 10.1186/s12885-021-09155-y
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-based dysphagia rehabilitation for adults with oesophageal cancer: a systematic review

Abstract: Background Dysphagia is prevalent in oesophageal cancer with significant clinical and psychosocial complications. The purpose of this study was i) to examine the impact of exercise-based dysphagia rehabilitation on clinical and quality of life outcomes in this population and ii) to identify key rehabilitation components that may inform future research in this area. Methods Randomised control trials (RCT), non-RCTs, cohort studies and case series we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 88 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…It is unclear whether the presence of a feeding tube may serve as a proxy for significant head and neck functional disability, such as due to late cranial neuropathy as suggested by the powerful association between active feeding tube use and neck disability, or whether the presence and use of the feeding tube itself increases the symptom burden. Regardless of directionality, current enteral feeding was associated with dramatically worse PROs, and proactive efforts to rehabilitate swallowing function may improve a variety of domains of health-related QOL . Continued innovations are needed in radiotherapy delivery, transoral surgery, and speech-language pathology to improve this essential clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether the presence of a feeding tube may serve as a proxy for significant head and neck functional disability, such as due to late cranial neuropathy as suggested by the powerful association between active feeding tube use and neck disability, or whether the presence and use of the feeding tube itself increases the symptom burden. Regardless of directionality, current enteral feeding was associated with dramatically worse PROs, and proactive efforts to rehabilitate swallowing function may improve a variety of domains of health-related QOL . Continued innovations are needed in radiotherapy delivery, transoral surgery, and speech-language pathology to improve this essential clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We recently conducted a systematic review which highlighted a paucity of evidence on dysphagia rehabilitation exercises both prior to and following EC surgery. 38 Future studies could evaluate the efficacy of exercises specifically targeting the most frequently impaired pathophysiological impairments and symptoms of dysphagia detected in this current study including oral and pharyngeal residue, reduced laryngeal elevation, reduced hyoid movement, and delayed swallow initiation. Oral and pharyngeal residue may potentially be caused by reduced lingual and pharyngeal strength 39 secondary to sarcopenia, a known cause of dysphagia acutely post-esophagectomy, 40 and therefore exercises targeting sarcopenic dysphagia may be beneficial to treat chronic symptoms.…”
Section: Discussionmentioning
confidence: 93%
“…Exercises to strengthen the suprahyoid muscles are clinically important for dysphagia prevention and rehabilitation. [ 21 , 22 ] Therefore, this study investigated the effect of the recently reported resistive swallowing exercise method using KT on the activation and thickness change of the suprahyoid muscles in older individuals living in the community.…”
Section: Discussionmentioning
confidence: 99%